Direct visualization of HIV-1-specific cytotoxic T lymphocytes during primary infection. - Wilson, J; Ogg, G; Allen, R; Davis, C; Shaunak, S; Downie, J; Dyer, W; Workman, C; Sullivan, S; Mcmichael, A; Rowland-Jones, S (2000)
OBJECTIVE: HIV-specific cytotoxic T lymphocytes (CTL) are believed to play an important role in containing viral replication throughout HIV-1 infection. Previous studies have attempted to quantify the HIV-1-specific CTL precursor frequency during primary HIV infection by using limiting dilution analysis, which almost certainly underestimates the true CTL frequency. Here we use a relatively new technique to quantify HIV-specific CD8 T cells in primary HIV infection. METHODS: We have used soluble tetrameric complexes of HLA class I molecules complexed with HIV epitope peptides to study the dynamics and frequency of HIV-specific CD8 T cells in relation to plasma viral load in early HIV infection, in three patients with a highly focused HIV-specific CTL response. RESULTS: We show that the frequencies of HIV-1-specific CD8 T cells in acute infection are significantly higher than previously documented and can be demonstrated well before full seroconversion. These studies also confirm the immunodominance of the B27-restricted response in HIV infection and demonstrate a close temporal relationship between the numbers of circulating HIV-specific CD8 T cells and viral load. CONCLUSIONS: These findings strongly suggest that HIV-1-specific CD8 T cells are responding directly to the level of viral replication in early HIV infection and are a major factor in its control. In addition, the data indicate that immunodominance for CD8 T-cell responses is established in the acute phase of HIV infection.